MEDIA LITERACY COMPETENCY-ORIENTED LIFE SKILLS FOR HIGH SCHOOL TEACHER IN THE CITY OF BANDUNG IN THE FACE OF MEA - Firman Aziz (JETL (Journal of Education, Teaching and Learning), 2016)
Use good media mass media as well as electronic media increases over time, especially with the presence of new media that is able to collect, process, and exchange information quickly. Research literacy competency media beorientasi life skills aims to describe the media literacy competency-oriented life skills which belonged to the high school teacher in the city of Bandung. Research methods using a descriptive qualitative approach method. The expected results are: (1) the discovery of the level and type of media literacy and competency (2) discovery of quality, factor endowments, and restricting the media literacy competency-oriented life skills teachers HIGH SCHOOL in Bandung. The results of the analysis of the data shows that the competence-based media literacy-oriented life skills teacher HIGH SCHOOL city of Bandung were still on secondary media literacy.